Assessment of Women's Knowledge about the Risks of Medication Use During Pregnancy in Al - Najaf Provence - Rashed, Maha Rasool; Aljebor, Murtadha Kanim Adea (South Eastern European Journal of Public Health, 2024)
Objective: The current study aims to assess women's knowledge about the Risks of Medication Use during Pregnancy and determine the relationship between Women's Knowledge about the Risks of Medication Use during Pregnancy and demographic characteristics. Methodology: A descriptive design /cross sectional study was conducted using analytical utilities to accomplish the stated objectives. In the time frame of 1st November 2023 to 19th July 2024. A non-probability sampling (Purposive sample) approach was used, based on the following criteria: pregnant women in any stage of the pregnancy, including the first, second, and third trimesters (primi gravida and multigravida). A sample of 250 pregnant women was chosen from those admitted to Al-Zahraa Maternity Teaching Hospital/ Al-Furat Teaching Hospital/ AL-Hakim Teaching hospital / primary Health care centers (Maternal, child, and infant care units). Results: the results show the level of knowledge differs significantly (P<0.05) according to level of education in which women who have institute and above exhibited the highest level of knowledge (MS=2.05). On the other hand, women whose husbands work in free jobs showed the highest level of knowledge (MS=1.97) while those whose husbands are retired exhibited the lowest level of knowledge (MS=1.50). Regarding gestational age, pregnant women within the (18-22) weeks exhibited the highest knowledge (MS=2.03). Conclusion: The study found that Women knew very little about the possible effects of some medications on fetal development, on the other hand the participants had little awareness of the safety of anticonvulsants and medications for the common cold and flu. Women had moderate levels of knowledge regarding the safety of using paracetamol (acetaminophen) for pain and fever during pregnancy.